2016
DOI: 10.1021/acs.chemrestox.6b00319
|View full text |Cite
|
Sign up to set email alerts
|

Aldo-Keto Reductase Regulation by the Nrf2 System: Implications for Stress Response, Chemotherapy Drug Resistance, and Carcinogenesis

Abstract: Human aldo-keto reductases (AKRs) are NAD(P)H-dependent oxidoreductases that convert aldehydes and ketones to primary and secondary alcohols for subsequent conjugation reactions and can be referred to as “phase 1” enzymes. Among all the human genes regulated by the Keap1/Nrf2 pathway, they are consistently the most overexpressed in response to Nrf2 activators. Although these enzymes play clear cytoprotective roles and deal effectively with carbonyl stress, their upregulation by the Keap1/Nrf2 pathway also has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 134 publications
1
74
1
Order By: Relevance
“…In this study, we found that the oxidative stress was over‐activated in the developing somites as well, and the expression of antioxidant genes including the Nrf2 was upregulated in presence of LPS (Figure 7). AKR can be regulated by the Nrf2 system 63 and retinaldehyde reduction can be performed by AKR 64 . This might be the mechanism of LPS‐induced excess ROS affected the RA production during embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the oxidative stress was over‐activated in the developing somites as well, and the expression of antioxidant genes including the Nrf2 was upregulated in presence of LPS (Figure 7). AKR can be regulated by the Nrf2 system 63 and retinaldehyde reduction can be performed by AKR 64 . This might be the mechanism of LPS‐induced excess ROS affected the RA production during embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…If these results could be confirmed in larger studies, than AKR1C1 and/or AKR1C3 may be considered to be included in prediction models in OPSCC and HNSCC . Low risk groups can then profit from de‐intensification of treatment protocols, whereas intermediate and high risk groups could be selected for other therapeutic options, such as inhibitors of the PI3K and NRF2 pathways including the AKR1C proteins …”
Section: Discussionmentioning
confidence: 99%
“…In this way PAH transhydrodiols would enhance their own genotoxicity by inducing expression of the AKR1Cs. 17 Because tobacco smoke thus can result in upregulation of AKR1C1 and AKR1C3 and 86% of patients in our cohort of 141 OPSCC were smokers (cohort II), we assessed if there was an association between these parameters by analyzing expression in the tumors with their adjacent epithelium. Interestingly, only in the adjacent epithelium there was prognostic difference between high and low stained samples (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%
“…BRIP1, BARD1, BRCA1, BRCA2). The therapeutic window for cyclophosphamide arises from tissue-specific expression of aldehyde dehydrogenases (ALDHs) which are the primary enzymes involved in cyclophosphamide inactivation (Cox et al, 1975); overexpression of ALDH1A1 and ALDH1B1 as well as aldo-keto reductases (AKRs) that metabolize cytotoxic products of cyclophosphamide (Penning, 2017) all conferred resistance in our screen. Detailed study of these genes is beyond the scope of this manuscript (full results are in Tables S8 and S9) but from these data we conclude that CRISPRi/a screening successfully identifies biologically relevant genes involved in resistance to RCHO.…”
Section: Crispri/a Screening Identifies Diverse Mechanisms Of Drug Rementioning
confidence: 99%